Kemampuan Siswa Kelas V SD Negeri 6 OKU dalam Meringkas Wacana dengan Menggunakan Model Cooperative Integrated Reading and Composition (CIRC) - Awalludin, Awalludin; Nilawijaya, Rita (UNIB Press, 2020)
The purpose of this study was to explain the ability of grade V students of SD Negeri 6 OKU in summarizing discourse using the Cooperative Integrated Reading and Composition (CIRC) learning model. The method used in this research is descriptive method. The techniques used are observation and test techniques. The results showed that the fifth grade students of SD Negeri 6 OKU were able to summarize discourse using the Cooperative Integrated Reading and Composition (CIRC) learning model. This is evidenced by the average value of the students' ability in summarizing discourse using the Cooperative Integrated Reading and Composition (CIRC) learning model which is 63.83% which is in accordance with the assessment indicators which are classified as sufficient. In detail, the results of this study are: suitability of the summary content is 56% (sufficient), accuracy of themes is 60.66% (sufficient), suitability of word counts is 90.66% (very good), and mechanics is 48% (poor). In addition, the results of observations in this study indicate that the teacher delivers material summarizing discourse that can be understood by students through the application of the CIRC learning model which is well done and easy to understand.